Pengaruh Bermain Terapeutik Storytelling Menggunakan Media Buku Cerita Bergambar terhadap Tingkat Kecemasan Anak Hospitalisasi - Rizqi Khalaliyah; Nopi Nur Khasanah; Kurnia Wijayanti (Pusat Riset dan Inovasi Nasional, 2025)
Hospitalization in preschool children often causes anxiety due to separation from parents, frightening medical procedures, and the unfamiliar hospital environment. Anxiety at an early age can have both short- and long-term negative impacts, such as refusal of medical treatment, difficulty cooperating with health professionals, and even traumatic experiences related to hospitals. One nursing intervention to reduce anxiety is play therapy, and storytelling is considered effective because it allows children to express their feelings and fears through imagination and enjoyable narratives. Objective: This study aimed to determine whether preschool children hospitalized in the Flamboyan Ward of Harapan Anda Islamic Hospital, Tegal, experienced a reduction in anxiety levels after being given therapeutic storytelling interventions using picture storybooks. Method: This study used a one-group pre-test–post-test design. Purposive sampling was employed to recruit 40 preschool children aged three to six years. Anxiety levels were measured using the DASS-42 questionnaire, consisting of 14 items related to anxiety. Data were analyzed using the Wilcoxon Signed Rank Test to compare pre- and post-intervention scores. Results: The findings showed that the majority of children after the intervention were in the normal category (67.5%), compared to 40% who experienced significant anxiety before the intervention. The Wilcoxon test produced a p-value of 0.000 (p < 0.05), indicating that therapeutic storytelling using picture storybooks significantly reduced anxiety levels in hospitalized preschool children. Conclusion: Therapeutic storytelling can be considered a simple, enjoyable, and effective non-pharmacological intervention for pediatric nurses to reduce anxiety among preschool children during hospitalization.